Toll-Like Receptor 3 in Liver Diseases - Shi Yin; Bin Gao (Gastroenterology Research and Practice)
Toll-like receptor 3 (TLR3) is a member of the TLR family that can recognize double-stranded RNA (dsRNA), playing an important role in antiviral immunity. Recent studies have shown that TLR3 is also expressed on parenchymal and nonparenchymal cells in the liver as well as on several types of immune cells. In this review, we summarize the role of TLR3 in liver injury, inflammation, regeneration, and liver fibrosis, and discuss the implication of TLR3 in the pathogenesis of human liver diseases including viral hepatitis and autoimmune liver disease.